Encyclopedia of women social reformers - Rappaport, Helen (Santa Barbara, Calif. : ABC-CLIO, 2001)
'This valuable contribution to women's studies includes the stories of more than 400 women from 64 countries and brings into the limelight many forgotten movements and personalities that have had major impacts on history. Readers will be inspired by the fascinating biographies.'--'Outstanding Reference Sources,' American Libraries, May 2002.
v. 1. A-L
Includes bibliographical references (p. 813-856) and index
Keywords: Women social reformers -- Encyclopedias; Women political activists -- Encyclopedias; Women's rights -- Encyclopedias